Piloting melt synthesis and manufacturing processes to produce c‐lifepo4: preface. (12th February 2019) - Patience, Gregory S.; Chaouki, Jamal; Latifi, Mohammad; Dollé, Mickaël; Chartrand, Patrice; Kasprzak, Wojciech; Sun, Xueliang; Sham, Tsun‐Kong; Liang, Guoxian; Sauriol, Pierre
Abstract : Since Goodenough's team laid the foundation to apply LiFePO4 as an alternative to lithium cobalt oxide for Li‐ion positive electrodes, [1, 2] Web of Science (WoS) [3] has indexed over 6000 articles related to lithium iron phosphate—LFP. Manufacturers synthesize LFP with both solid state and solvent assisted hydrothermal technology. Both have their advantages and disadvantages but society requires inexpensive batteries for automobile applications and fixed electrical storage. Here we scale up each step of the nascent melt synthesis process, which has the potential to displace the current commercial technology because of its superior economics related to raw materials. The research challenges include raw material selection, melt synthesis conditions, thermodynamics, micronization to form nano‐powders, followed by spray drying, and carbon coating.